2021
DOI: 10.3390/su131910982
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Satisfaction towards Green Products: Empirical Insights from Romania

Abstract: The current model of linear economy is causing accelerated consumption and an extensive use of natural resources that accentuates the effects of the current global environmental crisis. In this context, green products are becoming a key element in the transition to a sustainable consumption and production model. The main goal of this paper is to identify the factors predicting youth consumer satisfaction towards green products and to analyze the public perception of green brand products in Romania. Considering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 74 publications
6
28
2
2
Order By: Relevance
“…GPI is gaining wider interest from various worldly scholars since consumers became more mindful to obtain the products manufactured under green operations or environment-friendly production processes ( Biswas and Roy, 2015 ; Lakatos et al, 2021 ; Waheed and Zhang, 2020 ). It is the time to engage consumers as they want to be engaged consequently firms need to revise strategies to better align consumers’ interests along with organizational interests ( Lakatos et al, 2021 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…GPI is gaining wider interest from various worldly scholars since consumers became more mindful to obtain the products manufactured under green operations or environment-friendly production processes ( Biswas and Roy, 2015 ; Lakatos et al, 2021 ; Waheed and Zhang, 2020 ). It is the time to engage consumers as they want to be engaged consequently firms need to revise strategies to better align consumers’ interests along with organizational interests ( Lakatos et al, 2021 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…One way to demonstrate the results for GM is through the consumer purchasing behavior [81]. Knowing this relationship, it can be concluded that if organizations apply effective GM strategies, these will have a direct impact on green purchasing intentions and responsible effective purchases, positioning their brand and increasing their profitability [10,78,90,100].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the practices oriented to the development of green products and services, it is prioritized that the products to be marketed are ecological, from the acquisition of raw materials for their preparation to the form of the presentation and sale of the product, which is aimed at a segment of consumers concerned about the environment. In this regard, studies on the development of green products agree on the characteristics that these must have to be considered "environmentally friendly"; in this way, studies based on the circular economy are associated with this group of practices detected in the literature [101], as well as the evaluation of the impact of these products on the environment [10]. In the review of documents, it was found that the quality of the products and the manufacturing strategies have a causal relationship with various manifestations in consumer purchasing behaviors [25,64,[80][81][82][83], coinciding with the aforementioned studies that point out that the design of products in a circular economy must ensure a reduction in environmental damage through actions such as innovation in eco-design, recycling, product durability, the use of renewable resources, prevention of and reduction in waste during production, and the constant evaluation of the impact of products on the environment [10,101].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations